The rejection of industrial democracy by Berle and Means and the emergence of the ideology of managerialism. (February 2022) - Smith, Andrew; Tennent, Kevin; Russell, Jason
One distinctive feature of the American variant of capitalism is the near absence of any of the industrial democracy institutions found in many European firms. This article examines ideology as a factor behind the absence of industrial democracy institutions in the United States. It focuses on the early 1930s, when the ideology of managerialism was being formulated by Adolf Berle and Gardiner Means, the authors of a book that had a well-documented influence on American business culture. As the article shows, many American firms in the 1910s and 1920s experimented with worker representation systems that contemporaries called industrial democracy. Berle and Means were aware of these moves to democratize the American workplace, but they rejected all forms of industrial democracy. The article advances an explanation for their rejection and thereby contributes to our understanding why the United States did not take the path towards democracy within companies.